Collimator optimization for small animal radiation therapy at a micro-CT = Optimierung der Kollimatoren für die Kleintier-Strahlentherapie an einem Mikro-CT - Felix, Manuela; Glatting, Gerhard; Giordano, Frank Anton; Brockmann, Marc Alexander; Wenz, Frederik; Fleckenstein, Jens (Zeitschrift für medizinische Physik, 2017)
Purpose: In radiation therapy of small animals treatment depths range from a few millimetres to several centimetres. In order to spare surrounding organs at risk steep dose gradients are necessary. To minimize the treatment time, and therefore the strain to the animals, a high dose rate is required. A description how these parameters can be optimized through an appropriate choice of collimators with different source surface distances (SSD) as well as different materials and geometries is presented. Material and methods: An industrial micro-CT unit (Y.Fox, YXLON GmbH, Hamburg, Germany) was converted into a precision irradiator for small animals. Different collimators of either stainless steel (Fe) with cylindrical bores (SSD=42mm) or tungsten (W) with conical bores (SSD=14mm) were evaluated. The dosimetry of very small radiation fields presents a challenge and was performed with GafChromic EBT3 films (Ashland, Vayne, KY, USA) in a water phantom. The films were calibrated with an ionization chamber in the uncollimated field. Treatments were performed via a rotation of the objects with a fixed radiation source. Results: As expected, the shorter SSD of the W-collimators resulted in a (4.5±1.6)-fold increase of the dose rates compared to the corresponding Fe-collimators. The ratios of the dose rates at 1mm and 10mm depth in the water phantom was (2.6±0.2) for the Fe- and (4.5±0.1) for the W-collimators. For rotational treatments in a cylindrical plastic phantom maximum dose rates of up to 1.2Gy/min for Fe- and 5.1Gy/min for W-collimators were measured. Conclusion: Choosing the smallest possible SSD leads to a high dose rate and a high surface dose, which is of advantage for the treatment of superficial target volumes. For larger SSD the dose rate is lower and the depth dose curve is shallower. This leads to a reduction of the surface dose and is best suited for treatments of deeper seated target volumes. Divergent collimator bores have, due to the reduced scatter within the collimators, a steeper penumbra. The dosimetry of small kilovoltage beams with Gafchromic EBT3 films in a water phantom has proven successful.